In Vitro and In Vivo Characterization of Three Different Modes of Pump Operation When Using a Left Ventricular Assist Device as a Right Ventricular Assist Device. Issue 11 (24th March 2014) - Stevens, Michael C.; Gregory, Shaun D.; Nestler, Frank; Thomson, Bruce; Choudhary, Jivesh; Garlick, Bruce; Pauls, Jo P.; Fraser, John F.; Timms, Daniel
Abstract Dual rotary left ventricular assist devices (LVADs) have been used clinically to support patients with biventricular failure. However, due to the lower vascular resistance in the pulmonary circulation compared with its systemic counterpart, excessively high pulmonary flow rates are expected if the right ventricular assist device (RVAD) is operated at its design LVAD speed. Three possible approaches are available to match the LVAD to the pulmonary circulation: operating the RVAD at a lower speed than the LVAD (mode 1), operating both pumps at their design speeds (mode 2) while relying on the cardiovascular system to adapt, and operating both pumps at their design speeds while restricting the diameter of the RVAD outflow graft (mode 3). In this study, each mode was characterized using in vitro and in vivo models of biventricular heart failure supported with two VentrAssist LVADs. The effect of each mode on arterial and atrial pressures and flow rates for low, medium, and high vascular resistances and three different contractility levels were evaluated. The amount of speed/diameter adjustment required to accommodate elevated pulmonary vascular resistance (PVR) during support with mode 3 was then investigated. Mode 1 required relatively low systemic vascular resistance to achieve arterial pressures less than 100 mm Hg in vitro, resulting in flow rates greater than 6 L/min. Mode 2 resulted in left atrial pressures above 25 mm Hg, unless left heart contractility was near‐normal. In vitro, mode 3 resulted in expected arterial pressures and flow rates with an RVAD outflow diameter of 6.5 mm. In contrast, all modes were achievable in vivo, primarily due to higher RVAD outflow graft resistance (more than 500 dyn·s/cm5), caused by longer cannula. Flow rates could be maintained during instances of elevated PVR by increasing the RVAD speed or expanding the outflow graft diameter using an externally applied variable graft occlusion device. In conclusion, suitable hemodynamics could be produced by either restricting or not restricting the right outflow graft diameter; however, the latter required an operation of the RVAD at lower than design speed. Adjustments in outflow restriction and/or RVAD speed are recommended to accommodate varying PVR.